MELATIH REGULASI EMOSI PADA ANAK PRA SEKOLAH DENGAN BERMAIN: LITERATURE REVIEW - Desi Sukma Puspita Sari (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2022)
Emotion regulation plays a role in modulating the expression of emotions (positive and negative) in interacting with others according to social rules. Individuals who have good emotional regulation skills are able to see, evaluate, modify emotional reactions, are able to relieve and regulate the emergence of negative emotions. In preschoolers, the ability to regulate emotions is strongly influenced by the surrounding environment, namely the home and school environment. One method to train preschool children's emotional regulation is by playing. This writing is library research which is presented descriptively through several relevant literatures. The results of the review show that there are several methods used to train emotion regulation in preschoolers.